2020
DOI: 10.1182/bloodadvances.2020002337
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale circular RNA deregulation in T-ALL: unlocking unique ectopic expression of molecular subtypes

Abstract: Circular RNAs (circRNAs) are stable RNA molecules that can drive cancer through interactions with microRNAs and proteins and by the expression of circRNA encoded peptides. The aim of the study was to define the circRNA landscape and potential impact in T-cell acute lymphoblastic leukemia (T-ALL). Analysis by CirComPara of RNA-sequencing data from 25 T-ALL patients, immature, HOXA overexpressing, TLX1, TLX3, TAL1, or LMO2 rearranged, and from thymocyte populations of human healthy donors disclosed 68 554 circRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 64 publications
5
41
0
Order By: Relevance
“…To this aim, the current circRNA detection algorithms apply filtering procedures to remove FPs, but that may also reject true circRNAs (Zeng et al 2017; Chen et al 2015; Hansen 2018; Hansen et al 2016), increasing the number of FNs and the risk of overlooking circRNAs of interest, as suggested by our analysis. Moreover, the frequent practice of filtering out low count circRNAs to improve precision may result in the loss of differentially expressed elements in comparative studies, as demonstrated by systematic studies on gene expression (Zhu et al 2019)(Buratin et al 2020). Notably, unlike for FPs, experimental validations cannot amend the bias derived by FN errors.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, the current circRNA detection algorithms apply filtering procedures to remove FPs, but that may also reject true circRNAs (Zeng et al 2017; Chen et al 2015; Hansen 2018; Hansen et al 2016), increasing the number of FNs and the risk of overlooking circRNAs of interest, as suggested by our analysis. Moreover, the frequent practice of filtering out low count circRNAs to improve precision may result in the loss of differentially expressed elements in comparative studies, as demonstrated by systematic studies on gene expression (Zhu et al 2019)(Buratin et al 2020). Notably, unlike for FPs, experimental validations cannot amend the bias derived by FN errors.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA-encoded peptides were shown to function in the regulation of cell differentiation ( Legnini et al, 2017 ) and cancer progression ( Rossi et al, 2019 ). More and more, the key role of circRNAs in leukemogenesis is emerging ( Bonizzato et al, 2016 ; Jamal et al, 2019 ; Buratin et al, 2020 ) and perturbation of circRNA propagates in regulatory networks ( Bhat et al, 2020 ) and signaling pathways, with pleiotropic effects.…”
Section: Introductionmentioning
confidence: 99%
“…circUBAP2 (ubiquitin associated protein 2) facilitates CRC progression by sponging miR-199a to upregulate VEGFA which implies that circUBAP2 may be a potential therapeutic biomarker for CRC [ 51 ]. Furthermore, circZBTB44 (Zinc Finger and BTB Domain Containing 44) and circZNF609 are both upregulated in acute lymphoblastic leukemia [ 52 ] of which especially circZNF609 has a known oncogenic potential in multiple other cancers as well [ 53 , 54 , 55 , 56 , 57 ]. CircASPH (Aspartate Beta-Hydroxylase) expression is upregulated in lung adenocarcinoma [ 58 ] and, finally, circFUT8 (Fucosyltransferase 8) functions as a tumor suppressor in bladder cancer cells where low circFUT8 was associated with poor prognosis, high histological grade, and lymph node metastasis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%